Multiple-dose up-titration study to evaluate the pharmacokinetics, safety and antitumor activity of apatinib in advanced gastric adenocarcinoma - Wang, Yonggang; Wang, Chang; Zhang, Yanqiao; Hao, Jiqing; Yang, Nong; Wang, Jvfeng; Peng, Min; Liu, Tianshu; Zhang, Guifang; Zhan, Xianbao; Zeng, Shan; Zhang, Yifan; et al. (Frontiers in Oncology, 2022)
Background and Purpose: The objective of this study was to investigate the pharmacokinetics, safety, and antitumor activity of apatinib, a vascular endothelial growth factor receptor 2 inhibitor, in advanced gastric adenocarcinoma or gastroesophageal junction adenocarcinoma and evaluate the effect of dose titration on dosage optimization for individual patients. Methods: Patient with advanced gastric adenocarcinoma progressed after at least one line of chemotherapy were enrolled. Apatinib was given orally once daily starting at 500 mg for 14 days, then up-titrated to 750 mg for 14 days, and then proceeded to a maximum dose of 850 mg. Dose up-titration determination was based on toxicity. The 28-day treatment cycles continued until disease progression, intolerable toxicities, withdrawal of consent, or investigator’ decision. Results: A total of 60 patients were enrolled, with 17, 18, and 25 patients receiving a maximum dose of 500 mg, 750 mg, and 850 mg, respectively. The pharmacokinetic parameters varied considerably, with the interpatient coefficient of variation for steady state areas under the plasma concentration time curve (AUCss) and the mean maximum concentration of both > 50%. During 500 mg and 750 mg dosing stage, drug exposures in patients with a maximum dosage of 850 mg were lower than in those not titrated to 850 mg. Patients with total gastrectomy exhibited significantly lower AUCss than patients with partial or no gastrectomy (p = 0.004 and 0.032, respectively). Toxicities were tolerable, and disease control rate was 39.5% (95% CI 25.0%‒55.6%). Conclusions: Apatinib dose titration based on toxicity could be used in clinical practice to provide optimal dosage for individual patients.